(4 - 5x)(2 + x) = -(4+ 5x2)
8 + 4x - 10x -5x² = -4 -5x²
4x - 10x = - 4 - 8
-6x = - 12 / /(-6)
x = 12/6
x = 2
4x2 - 2x = (2x + 1)(2x - 3)
4x² - 2x =4x² - 6x + 2x - 3
-2x - 2x + 6x = -3
2x=-3 / / 2
x = - 3/2
x= - 1,5
3x(2x + 5) = (x+3)(6x + 1)
6x² + 15x = 6x² + x + 18x + 3
15x - 18x - x = 3
-4x = 3
x = - 0,75
Ex - x - (4x + 1)] = 1 - 41
tu nie wiem o co chodzi chyba jest nie pełne ale z tego co jest wychodzi, że
Ex - 5x - 1
f(3x - 1) - 12x +3(x - 2)) = 1
3fx - f - 12x + 3x - 6 = 1
3fx - f - 9x = 7
tu chyba też jest nie pełny przykład